Optimizing tobacco quality and yield through the scientific application of organic-inorganic fertilizer in China: a meta-analysis - Zhu, Ruixuan; He, Shijie; Ling, Huarong; Liang, Yongjin; Wei, Beilei; Yuan, Xiaomai; Cheng, Wuyang; Peng, Bo; Xiao, Jinglin; Wei, Jianyu; He, Yi; Xiao, Heyou; et al. (Frontiers in Plant Science, 2024)
China is the largest producer and consumer of tobacco (Nicotiana tabacum L.) in the world, and the cultivation and production of tobacco have extremely high economic value and social influence. Applying organic-inorganic fertilizer is a key strategy for boosting tobacco yield and quality. This meta-analysis examines 632 observations from 169 articles to determine the precise influence of organic-inorganic fertilizer on tobacco. It evaluates the effects of different tobacco types and fertilizer compositions on yield and quality after fertilizer application. The application of organic-inorganic fertilizer significantly increased the yield (3.4%), but it mainly improved the balance of chemical composition and enhance the quality of tobacco (high-grade tobacco, 10.3%; reducing sugar content, 5.5%; nicotine content, –5.6%). The Y85 and Y87 varieties showed the most positive response to fertilization, with yield increases of 5.59% and 5.82%, respectively, and high-grade tobacco leaf rates increased by 14.92% and 11.04%, respectively. Fertilizers with a low organic nitrogen ratio (15%-30%) are more effective for increasing yield, while those with a medium to high ratio (50%-60%) improve tobacco’s chemical quality. The application of organic-inorganic fertilizer balanced the nutrient distribution within the tobacco plants, leading to simultaneous increases in both yield and quality. This study quantitatively assessed the effects of organic-inorganic fertilizer on the yield and quality of tobacco and provides a solid theoretical foundation for the scientific and high-quality application of organic-inorganic fertilizer in various tobacco cultivation areas.